PEMBERDAYAAN GURU-GURU SD SEBAGAI UPAYA MENINGKATKAN KUALITAS PEMBELAJARAN SENI BUDAYA DAN PRAKARYA (SBdP) - Abd. Hafiz; Wisdiarman Wisdiarman; Suib Awrus; Ramalis Hakim (Jurusan Seni Rupa, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2019)
Teachers in Padang City Elementary Schools, especially in the Gugus V Elementary School, Padang Timur District, experienced problems in improving the quality of learning in the Culture and Arts and Crafts, thus affecting the achievement of student learning outcomes. One of the efforts in improving the quality of learning, teachers need to improve their learning by implementing CAR. In general, the East Padang Elementary School Group V teacher has not been able to do a CAR to improve their learning. Teachers are not implemented by CAR, because generally they do not master CAR and innovative learning strategies / models that can be used as a solution in improving learning. The solution offered to solve this problem is to provide training activities to teachers about innovative learning strategies and the implementation of CAR. The results of this activity are 1) 84.62% of teachers have mastered the learning strategies of arts and culture and crafts well, 2) 80.76% of teachers have mastered the implementation of CAR well, both theory and practice. Thus it can be concluded that generally teachers in elementary schools have mastered SBdP learning strategies and the implementation of CAR. For this reason, elementary school teachers are expected to be able to improve learning, especially learning in the Culture and Arts and Crafts, so that learning outcomes can be improved.